Effect of ß-glucan from Euglena gracilis as an antioxidant on goat semen cryopreservation - Ustuner, B; Soylu, MK; Sengul, E; Karakci, D; Gokce, E; Aktar, A; Ak Sonat, F; Cimen, T; Huraydin, O; Yılmaz, MM; Nur, Z (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to determine the influence of different doses of β-glucan on post-thaw spermatological parameters, lipid peroxidation, and total antioxidant activity of buck semen. In the non-breeding season, semen was collected from bucks twice weekly. After then, ejaculates were pooled and divided into four equal aliquots: β-glucan concentrations of 1 mM (βG1), 2 mM (βG2), and 4 mM (βG4), and a control group without antioxidants. Each sample group was diluted for cryopreservation using a dilution method involving two steps. The experimental groups were then evaluated for several parameters including sperm motility, plasma membrane functional integrity [hypoosmotic swelling test (HOST)], damaged acrosome rate [FITC-Pisum sativum agglutinin (FITC-PSA)], DNA integrity [terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL)], mitochondrial membrane potential using JC-1, evaluation of lipid peroxidation, and determination of total antioxidant activity. The post-thaw motility and plasma functional integrity of the control group were significantly lower than those values in the βG groups (P < 0.05). Although the numerically greatest acrosome damage was detected in the control group, it was only statistically different from βG1 and βG4 (P<0.05). While the DNA fragmentation rate of the control group was higher than βG4 group (P<0.05), it was similar to βG1 and βG2 groups (P>0.05). There was no statistical difference among all the groups regarding low mitochondrial membrane potential, MDA, and TAC rates. In line with our results, supplementation of 1mM, 2 mM and 4 mM β-glucan to freezing extender improves the post-thaw spermatological characteristics of goat semen.